(untitled) (Research, Society and Development, 2021)
The Umbu is a native fruit from the northeast region of acidic flavor and rich in vitamin C, however, has a high content of waste due to its extreme perishability. Drying is a known method for decreasing food water activity and extending fruit shelf life, allowing for extended storage and longer product stability and longevity for longer shelf life. Among the drying media, which can be dried on the foam layer, which is a conservation method that allows food conservation to be conserved, preserving quality even at low production costs. This research aimed to perform the drying in the Umbu pulp foam layer, using an analysis of the drying kinetic curves, and using an experimental design, studying the effects of the input variables: drying temperature and recovery time. foam, on the response variables: ascorbic acid and total titratable acidity. A statistical analysis did not generate a statistically significant model at the 95% confidence level for the response variables that were studied after the experimental matrix studied.